'War on Terror' in our backyard: effects of framing and violent ISIS propaganda on anti-Muslim prejudice. (1st September 2016) - Hatton, Arthur T.; Nielsen, Michael E.
ABSTRACT: Framing metaphors for counterterrorism have been analyzed theoretically but their effect has not yet been fully understood empirically. One framing metaphor that has been employed for counterterrorism is a 'War on Terror'. The present study examined the effect of using the phrase 'War on Terror' on support for security policies that unfairly target Muslims. We manipulated the frame to make federal action or community action salient. Additionally, we tested the effect of the release of Islamic State of Iraq and the Levant (ISIL/ISIS/Daesh, hereafter ISIS) propaganda films by collecting data before and after the February 2015 video featuring the execution of 21 Egyptian Copts by a Libyan ISIS group. We found that, after the video was released, a community-based framing of the 'War on Terror' significantly increased support for anti-Muslim security policies. We also examined the demographics of those who had seen ISIS videos versus those who had not and the factors that predicted whether participants were distressed by the videos. Those who had seen the videos were more likely to be male and have personal ties to the military or law enforcement. Those who were distressed by the videos were more likely to be politically conservative, female, younger, and have personal ties to the military or law enforcement.